Pengaruh Kontrasepsi Hormonal terhadap Disfungsi Seksual pada Wanita - Viola Arisanti (Yayasan Pendidikan Medika Indonesia, 2021)
Contraception are devices or methods used to revent pregnancy. Contraception is divided into two, hormonal and non-hormonal contraception. In Indonesia, hormonal contraception. provide the largest contribution in reducing birth rates, but until now there has not been found an ideal contraception free of side effects. Contraception, especially the hormonal type, can interfere with a woman's sexual function. Female sexual function was measured using the FSFI (Female Sexual Function Index) questionnaire. Sexual dysfunction is a sexual function disorder that is often associated with the use of hormonal contraception. Sexual dysfunction can have a negative impact on quality of life and emotional health regardless of age.